Analisis Hadis terhadap Fenomena Filial Crisis Kontemporer - Nadirotul Munawaroh; Muhammad Alif; Salim Rosyadi (Al-Mu'tabar, 2025)
The phenomenon of filial crisis—the weakening of children's respect, care, and responsibility toward their parents—has emerged as a significant moral and social challenge in the modern era. This crisis is driven by shifting cultural values, the rise of individualism, and the disruption of traditional family roles in contemporary society. This article aims to analyze the phenomenon from the perspective of the Prophet Muhammad’s hadiths using a thematic and contextual approach. Hadiths addressing filial piety (birr al-wālidayn), prohibitions against disobedience, and encouragement to honor and care for elderly parents are examined in light of today’s social realities. The study finds that these hadiths emphasize not only ethical norms—both vertical (relationship with God) and horizontal (social relationships)—but also provide a spiritual foundation for preserving family harmony. By recontextualizing these prophetic values, Islam offers both normative and practical solutions to address the filial crisis. This study recommends integrating hadith-based values into character education curricula and reinforcing family-based social systems.